Serum Lactate Dehydrogenase (LDH) Level in Severe Preeclampsia - Afroz, Rukhsana; Akhter, Qazi Shamima; Sadia, Halima; Sultana, Sharmin (Journal of Bangladesh Society of Physiologist, 2016)
Background: Serum LDH level is an useful biomarker for cellular injury which may reflect the severity of preeclampsia and its level might be a guideline for the management of patient. Objective: To assess serum LDH level in preeclamptic women. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College (DMC), Dhaka from January to December 2014. Total 105 pregnant women during third trimester (28-40 weeks) aged 18 to 35 years were selected from the Department of Obstetrics & Gynecology of DMC Hospital, Dhaka for this study. Among them, 35 were mild preeclamptic and 35 were severe preeclamptic women. Age matched 35 normotensive pregnant women were control. Serum LDH level was estimated by continuous spectrophotometric method. Results: In this study, serum LDH level was significantly higher (P<0.001) in preeclamptics compared to those of control. Again, this value was significantly higher in severe preeclamptics than those of mild preeclamptics. Moreover, 82.9% mild preeclamptic and 91.4% severe preeclamptic women had abnormally elevated serum LDH level (>200 U/L). Conclusion: From this study, it can be concluded that elevated serum LDH level is associated with severity of preeclampsia. Bangladesh Soc Physiol. 2015, December; 10(2): 71-75